Normalized Cortisol Reactivity Predicts Future Neuropsychological Functioning in Children With Mild/Moderate Asthma - Dinces, Sarah M.; Rowell, Lauren N.; Benson, Jennifer; Hile, Sarah N.; Tang, Akaysha C.; Annett, Robert D. (Frontiers in Psychology, 2019)
Cortisol reactivity to adrenocorticotropic hormone (ACTH) has been associated with neuropsychological processes including attention and memory in children with asthma. While cortisol reactivity to a psychological stressor is often considered a measure of current neuroendocrine functioning, this study examines the association of the cortisol reactivity and subsequent neuropsychological functioning. Using prospective data from the Childhood Asthma Management Program (CAMP), we explored the predictive ability of cortisol reactivity to ACTH and children’s later attention and memory using traditional and an alternative cortisol reactivity (normalized cortisol) measures. Cortisol reactivity was assessed at study entry and 1-year follow-up, and neuropsychological functioning was assessed at 3-year follow-up. Cortisol reactivity was assessed through plasma cortisol concentrations collected at baseline (CORTBASELINE) and 30 minutes post-ACTH challenge (CORTPOST-ACTH). An alternative measure of cortisol reactivity was developed through post-ACTH stimulation cortisol, normalized by cortisol by baseline (CORTNORM-ACTH). CORTBASELINE positively predicted year 3 attention, while CORTNORM-ACTH negatively predicted attention, suggesting convergence of cortisol variables in prediction of neuropsychological function. Year 1 CORTACTH positively predicted child memory at year 3; Year 1 CORTNORM-ACTH negatively predicted year 3 sustained attention. These findings demonstrate that HPA reactivity, including the application of normalized cortisol reactivity, can predict subsequent neuropsychological functioning of children with mild to moderate asthma.